단절과 점진의 화해 : 경로생성과 경로조정의 관점에서 본 노동정책 변동에 관한 연구 - 한종희; Han Chonghee (한국행정연구, 2018)
본 연구는 1987년 이후 현재에 이르는 30여년 간의 우리나라 노동정책 변동에 대한 분석이다. 노동정책 변화를 단절과 점진적 변동의 동학으로 보았다. 이는 제도 변화에 구조와 행위자의 상호작용에 방점을 두기 위함이다. 정책 변동은 신제도주의 관점을 근간으로 하면서, 경로생성 (path generation)과 경로조정(path alteration)의 개념을 활용하여 문헌분석을 중심으로 이루어졌다. 단절적 균형론이 시사하는 바, 새로운 경로생성에 따른 단절적 변동을 설명하기 위해 1987년 민주화, 1997년 IMF 경제위기, 즉 ‘외부 충격’(중대국면)에 주목했고, 경로조정을 통한 점진적 변동은 중대국면이 형성된 이후의 노·사·정의 상호작용, 전략적 선택에 초점을 두었다. 연구 결과, 노조설립의 자유화, 노사정위를 통한 노조의 정책참여 그리고 정리해고 합법화는 단절적 변동으로, 임금임상(전환), 근로시간 단축(전환), 유연근무제(가겹), 비정규직 보호(전치), 성과연봉제(표류)은 점진적 변동으로 분석 되었다. The study is about the analysis of labor policy changes for the past three decades in Korea. They are regarded as the dynamics of punctuated and marginal changes, the bases of which focus on the interactions between the structure and actors involved. It is based on new institutionalism theoretically as well as text analysis methodologically using the concept of path generation and path altering. As Punctuated Equilibrium Theory suggests, external shocks called critical junctures create a new path through which punctuated changes have occurred. They include the democratization of 1987, the so-called IMF economic crisis of 1997. However, the newly generated path is subject to alteration due to the strategic choices of policy actors, causing policies to change gradually. Good examples in terms of punctuated changes are liberalization of unions, involvement of union in policy-making process, and legalization of lay-offs. The marginal changes include wage increase (conversion), working hour reduction (conversion), flexible work schedule system (layering), performance-based pay system (drift), and irregular workers protection law (displacement).